Coronary artery risk factors in polycystic ovary syndrome (PCOS): are Sri Lankan women at greater risk ? - Wijeyaratne, C.N.; Gunewardena, A.U.A.; Pathmakumara, A.; Nirantharakumar, K.; Barth, J.H.; Collins, M.; Balen, A.H. (The Sri Lanka College of Obstetricians and Gynaecologists, 2003)
BACKGROUND: PCOS is associated with risk factors for premature atherosclerosis. OBJECTIVE: To determine risk factors for coronary artery disease (CAD) among Sri Lankans with PCOS. METHOD: Cross sectional observational case control study of consecutive consenting Sri Lankans with PCOS (80) and controls (45) attending a specialist endocrine clinic in Colombo. OUTCOME MEASURES: BMI & waist: hip ratio (WHR), prevalence of metabolic disease, resting blood pressure, degree of insulin resistance, plasma lipids and fasting plasma total homocysteine (Hcy). RESULTS: Among the PCOS women, 5/80 (6.25 percent) had hypertension, 6/80 (7.5 percent) Type 2 diabetes. PCOS versus controls Mean age 27.3 ñ1.7 vs. 33 ñ 4.7 (p =0.003); BMI 26.3 ñ 0.95 vs. 23.1 ñ 0.06 (0.04); WHR 0.95 ñ 0.01 vs. 0.79 ñ 0.03 (p=0.03). Excluding hypertensives mean Systolic BP 130 vs. 110 (p=0.02) & Diastolic BP 86 vs. 70 (p=0.04) mm Hg; Insulin sensitivity 0.305 ñ 0.011 vs. 0.333 ñ 0.014 (p =0.0006); Fasting cholesterol 6.1 ñ 0.03 vs. 5.8 ñ 0.01 (p=0.l4),Triglycerides 3.3 ñ 0.2 vs. 2.6 ñ 0.1 (p=0.03), HDL 1.16 ñ 0.1 vs. 1.4 A 0.2 (p=0.01) mmol/l & Hey 10.18 ñ 1.9 vs. 9.0 ñ 3.8 (p=0.001)mmol/l. with significant correlation of Hcy with central obesity and insulin resistance. CONCLUSIONS: This is the first report of a high prevalence of central obesity, increased insulin resistance, abnormal lipids and elevated plasma Hcy (risk factors of CAD) in a cohort of Sri Lankans with polycystic ovary syndrome, which bear major implications on their long term risks of coronary artery disease. FUNDING: Association of Physicians of Great Britain and Ireland and Special Trustees, General Infirmary at Leeds UK.
Keywords: PCOS; Sri Lankan